High-resolution planktonic foraminiferal analysis from the Cretaceous-Tertiary boundary at Ain Settara (Tunisia): Evidence of an extended mass extinction - Luciani V. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2002)
The Ain Settara section, located in the Kalaat-Senan area of north^central Tunisia, spans the Cretaceous/Tertiary (K/T) boundary which is characterized by a red layer and a thin non-bioturbated boundary clay. Sediment accumulation across the K^T boundary at Ain Settara was probably interrupted by three short hiatuses and/or condensed sedimentation. The first hiatus occurs at the top of the CF1 Zone; the second hiatus/condensation occurred just below the boundary clay and the third hiatus at the P0/P1a boundary, in the earliest Danian. These hiatuses are marked by weak unconformities, bioturbation and sudden disappearances/appearances of species which are known to disappear/evolve sequentially in continuous sections. Quantitative high-resolution planktonic foraminiferal analysis across zones CF1(upper), P0 and P1a (1) reveals an extended and selective mass extinction. All 41% of the species which disappeared at or below the K/T boundary are rare to very rare and primarily ecologically specialized keeled deeper-dwelling tropical^subtropical forms (Globotruncana, Globotruncanita, Gublerina, Planoglobulina, Rosita (Contusotruncana), Racemiguembelina). Their combined relative abundance varies between 10% and 15% of the total population at the end of the Maastrichtian. The K/T crisis thus appears more catastrophic when viewed in tropical^subtropical assemblages and based on analysis of larger species (s200 Wm) which preferentially includes the more specialized forms, though, in fact, the K^T mass extinction actually involved a relatively small part of the foraminiferal population in terms of relative abundance. The pattern of extinction and changes in dominant population at Ain Settara appear to be very similar to the planktonic foraminiferal turnover of the other north-central Tunisian sections (El Kef, Elles). The selective mass extinction pattern suggests that the catastrophic effects of the bolide impact superimposed those related to long-term environmental changes, such as variations in temperature, sea-level and ...